STREPTOCOCCUS INFECTION IN CHILDREN TODAY - Pikul, E.V. (World of Medicine and Biology, 2014)
In the thesis presents an analysis based literature, the causes and clinical manifestations streptococcosis children. In particular, the author pays great attention to scarlet fever as one of the first manifestations of streptococcal infection.